Equipping for service : Christian leadership in church and society. - Jørgensen, Knud (Regnum practitioner series., 2012)
Equipping for Service, Christian Leadership in Church and Society, by Knud Jorgensen, is written out of decades of experience leading churches and missions in Ethiopia, Geneva, Norway, and Hong Kong. Combining the teaching of Scripture with the insights of contemporary management philosophy, he writes in his introduction, "The intention has been to challenge towards a leadership relevant for work in church and mission, and in public and civil society, with special attention to leadership in church and organisation."